2002
DOI: 10.1080/09540120220133099
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian dental students' knowledge and attitudes towards HIV infection

Abstract: The purpose of this study was to investigate a group of Brazilian dental students' knowledge about HIV infection, the infection control measures utilized by the dental students, and students' attitudes towards treating HIV/AIDS patients. The study population consisted of 250 dental students from Universidade Federal da Bahia, Brazil, who were treating patients in clinics of the university and extra-mural rotations at the time of the study. The survey instrument was a self-administered questionnaire which consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
68
5
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 2 publications
13
68
5
3
Order By: Relevance
“…Although reports from other countries showed that female dentists appear to follow infection‐control measures more closely than their male colleagues, our results found that female dentists are less likely to agree to treat a simulated patient with a blood‐borne disease in general compared with a male dentist. This may lead us to assume that this refusal reflects the exaggerated fear of transmission of infection among female dentists owing to the social stigma attached to blood‐borne diseases, especially in HIV/AIDS.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Although reports from other countries showed that female dentists appear to follow infection‐control measures more closely than their male colleagues, our results found that female dentists are less likely to agree to treat a simulated patient with a blood‐borne disease in general compared with a male dentist. This may lead us to assume that this refusal reflects the exaggerated fear of transmission of infection among female dentists owing to the social stigma attached to blood‐borne diseases, especially in HIV/AIDS.…”
Section: Discussioncontrasting
confidence: 84%
“…Thirty‐four per cent of respondents declined, and 16% were hesitant to accept, a request to schedule an appointment for simulated patients who identified themselves as having blood‐borne diseases. This may reflect negative attitudes of dentists towards patients with blood‐borne infections or lack of confidence in their ability, or their practice's readiness, to treat such patients. This negative attitude may force patients infected with HIV or HBV to conceal their infection from their treating dentists for fear of being denied dental treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with a study done in Brazil where majority of the dental students considered every dental patient a potential HIV carrier and were aware of the association between HIV and Kaposi's sarcoma (92.5%), oral candidiasis (90.3%) and oral hairy leukoplakia (52.7%). 13 A study done in Tanzania reported that the clinical finding of oral hairy leukoplakia was found to have a predictive value of 100% and 95% for the presence AIDS and HIV infection, respectively. 14 Thus, there is great significance in the presence of oral hairy leukoplakia which was underestimated by the students in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that many dentists choose to refer patients identified with positive sero‐conversion elsewhere, which can make it difficult for persons with HIV to access dental care 5 . This preference has been attributed to low levels of knowledge among dentists both in practice and within training institutions in which the dental training curriculum does not emphasise the management of people living with HIV/AIDS (PlwHA) 6–9 . Consequently, oral health care workers have maintained negative attitudes towards PlwHA, resulting in inadequate identification of oral lesions in such patients 10 .…”
mentioning
confidence: 99%